SISTEM PENGENDALIAN SUHU DAN KELEMBAPAN MENGGUNAKAN KONTROLER PID PADA PLANT INKUBATOR BAYI - Rafa Raihan Fadilla; n/a Rahmadwati; Moch. Rusli (Jurnal Mahasiswa TEUB, 2023)
Many infant mortality rates are due to premature events. Premature babies will have difficulty regulating their body temperature. If not treated properly, the baby will suffer hypothermia. To overcome this, you can use a baby incubator as a heater. The baby incubator's temperature is maintained within normal limits of around 33°C–35°C with a relative humidity of 40% RH-60% RH to help stabilize the baby's body temperature. However, in most baby incubators, the system is still controlled manually. So an automatic temperature and humidity control system is needed in the baby incubator. For temperature control, a PID controller is used with a value of Kp = 11,4, Ki = 0,03, and Kd = 1100,1, while humidity control is used with an on-off controller. According to theresults of the PID controller experiments, steady state error was 0,65%, settling time (5%) 5,81 minutes, settling time (2%) 7,75 minutes, and settling time (0,5%) 9,7 minutes. Meanwhile, the results of the humidity experiments with a limit of 58% RH–62% RH, the response obtained was a settling time of 3,4 minutes. Keywords— Premature Babies, Incubator, Ziegler Nichols. DAFTAR PUSTAKA[1] Lawn, J. E., dan Kinney, M. 2014. Preterm Birth: Now the Leading Cause of Child Death Worldwide. Science Translational Medicine. 6 (263): 1-3.[2] Zermani, M. A., Feki, E., dan Mami, A. 2014. Building Simulation Model of Infant Incubator System with Decoupling Predictive Controller. IRBM. 35 (4): 189-201.[3] Singla, S. K., dan Singh, V. 2015. Design of a Microcontroller Based Temperature and Humidity Controller for Infant Incubator. Journal of Medical Imaging and Health Informatics. 5 (4): 704-708.[4] Visscher, M. O., Adam, R., Brink, S., dan Odio, M. 2015. Newborn Infant Skin: Physiology, Development, and Care. Clin Dermatol. 33 (3): 271-280.[5] Hutagaol, H. S., Darwin, E., dan Yantri, E. 2014. Pengaruh Inisiasi Menyusu Dini (IMD) terhadap Suhu dan Kehilangan Panas pada Bayi Baru Lahir. Jurnal Kesehatan Andalas. 3 (3): 332-338.[6] Wulandari, R. A., dan Praborini, A. 2018. Anti Stres Menyusui. Edisi ke-1. Kawan Pustaka. Jakarta.[7] Hammarlund, K., Nilsson, G. E., Oberg, P. A., dan Sedin, G. 1977. Transepidermal Water Loss in Newborn Infants. I. Relation to Ambient Humidity Site of Measurement and Estimation of Total Transepidermal Water Loss. Acta Paediatrica. 66 (5): 553-562.[8] Rutter, N. 2000. Clinical Consequences of an Immature Barrier. Semin Neonatal. 5 (4): 281-287.[9] Latif, A., Widodo, H. A., Atmoko, R. A., Phong, T. N., dan Helmy, E. T. 2021. Temperature and Humidity Controlling System for Baby Incubator. Journal of Robotics and Control. 2 (3): 190-193.[10] Hasan, A. 2019. Sistem Monitoring Suhu dan Kelembaban pada Inkubator Bayi Berbasis Internet of Things (IoT). Skripsi. Fakultas Teknik Universitas Semarang, Semarang.[11] Yudaningtyas, E. 2017. Belajar Sistem Kontrol Soal & Pembahasan. Edisi ke-1. Universitas Brawijaya Press. Malang.[12] Ogata, K. 1997. Teknik Kontrol Automatik (Sistem Pengaturan). Edisi ke-1. Erlangga. Jakarta.[13] Ogata, K. 2010. Modern Control Engineering. Edisi ke-5. Prentice Hall. New Jersey